MUSLIM KELAS MENENGAH DI MALAYSIA: DEFINISI SERTA SUMBANGAN DALAM BIDANG EKONOMI DAN POLITIK (Middle Class Muslim in Malaysia : Definition and Their Contributions to Economics and Politics) - Mujani, Wan Kamal; Kasri, Allawati (Journal of Al-Tamaddun, 2012)
he ?class? structure, especially the ?middle class? is a concept that has always been a debate in the world of social sciences nowadays. ?Class? is a term that is difficult to define because it is regarded as something that can be both relative and subjective. Islam itself does not recognize the existence of classes in the structure of its society. Although the concept of ?class? does not exist in Islam, the study of it should be highlighted in order to fully understand the use of this concept in the context of Muslim societies, especially in Malaysia. In addition, not a lot of specific studies on Muslim middle class in Malaysia have been brought to light. Therefore, this paper is presented to study the Muslim middle class in Malaysia, consisting of Malays, Chinese and Indians. All three groups have contributed greatly towards the development of the country, whether in economics, politics, or social aspects. However, this article will only focus on the contribution of the Muslim middle class in economics and politics alone. Their contribution in the economic field can be seen through their involvement in businesses and industries throughout the nation. The involvement of all three groups, especially in professional fields, management, and administration has helped the country in increasing employment and reducing unemployment. Besides that, these people also have high purchasing power and are able to develop a good culture of consumerism within the community. Indirectly, it will accelerate the development and progress of countries, namely through an increase in demand for certain goods and services. Their contributions in politics can be seen through their participation in the political parties in Malaysia such as the United Malay National Organization (UMNO), Malaysian Chinese Association (MCA), Malaysian Indian Congress (MIC), Malaysian Indian Muslim Congress (KIMMA) and other non-government agencies.